EFEKTIVITAS PROMOSI KESEHATAN DALAM MENINGKATKAN SELF EFFICACY DAN PENGETAHUAN TENTANG IMS, HIV DAN AIDS PADA SISWA SMA - Erike Yunicha Viridula; Siswi Wulandari (Jurnal Ilmu Keperawatan dan Kebidanan, 2022)
HIV and Sexually Transmitted Infections (STIs) are still a major concern worldwide as the number of HIV and Sexually Transmitted Infections (STIs) in adolescent age groups continues to rise. The purpose of the study is to find out the effectiveness of health promotion in improving self efficacy and knowledge about STIs, HIV and AIDS of High School Plus students Hidayatut Thullab Semen Kediri Regency. The research method used is quasi-experimental. The sample in this study was the entire 2nd grade at SMA Plus Hidayatut Thullab Semen Kediri Regency totaling 74 students, divided into 2 groups, namely groups with leaflet methods (37 people) and groups with video methods (37 people). Variables in the study are independent variables (effectiveness of health promotion in the form of leaflet methods and video methods) and dependent variables (self efficacy and knowledge of STIs, HIV and AIDS). Research measuring instruments use checklists and are analyzed with independent sample t test tests. The results showed there were significant differences in self-efficacy and knowledge between the groups given the video compared to leaflets. In self efficacy about STIs get a p value of 0.017, self efficacy about HIV and AIDS gets a p value of 0.030, yearists about STIs get a p value of 0.010 and knowledge about HIV and AIDS get a p value of 0.001. The health promotion organizing team needs to implement effective methods and attract students' interest in following the materials provided.